I may be wrong but I got x³- 2 + 12.
<span>So we have a polynomial 5x^5-9x^3+2x^11+6 and we are wondering what is its degree, leading coefficient, number term and the constant term. The degree of a polynomial is its highest power so here that is 11. Leading coefficient is the term with the highest degree of a polynomial and here thats 2. Number of terms is 4 because that many numbers are in this polynomial and the constant term is 6 beccause it is a constant. </span>
Answer:
0.3108 is the probability that the sample mean is between 7.8 and 8.2 minutes.
Step-by-step explanation:
We are given the following information in the question:
Mean, μ = 8 minutes
Standard Deviation, σ = 2.5 minutes
Sample size, n = 25
We are given that the distribution of time spent is a bell shaped distribution that is a normal distribution.
Formula:
![z_{score} = \displaystyle\frac{x-\mu}{\sigma}](https://tex.z-dn.net/?f=z_%7Bscore%7D%20%3D%20%5Cdisplaystyle%5Cfrac%7Bx-%5Cmu%7D%7B%5Csigma%7D)
Standard error due to sampling =
![=\dfrac{\sigma}{\sqrt{n}} = \dfrac{2.5}{\sqrt{25}} = 0.5](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B%5Csigma%7D%7B%5Csqrt%7Bn%7D%7D%20%3D%20%5Cdfrac%7B2.5%7D%7B%5Csqrt%7B25%7D%7D%20%3D%200.5)
P(sample mean is between 7.8 and 8.2 minutes)
![P(7.8 \leq x \leq 8.2)\\\\ = P(\displaystyle\frac{7.8 - 8}{0.5} \leq z \leq \displaystyle\frac{8.2-8}{0.5})\\\\ = P(-0.4 \leq z \leq 0.4})\\\\= P(z < 0.4) - P(z < -0.4)\\\\= 0.6554 -0.3446= 0.3108](https://tex.z-dn.net/?f=P%287.8%20%5Cleq%20x%20%5Cleq%208.2%29%5C%5C%5C%5C%20%3D%20P%28%5Cdisplaystyle%5Cfrac%7B7.8%20-%208%7D%7B0.5%7D%20%5Cleq%20z%20%5Cleq%20%5Cdisplaystyle%5Cfrac%7B8.2-8%7D%7B0.5%7D%29%5C%5C%5C%5C%20%3D%20P%28-0.4%20%5Cleq%20z%20%5Cleq%200.4%7D%29%5C%5C%5C%5C%3D%20P%28z%20%3C%200.4%29%20-%20P%28z%20%3C%20-0.4%29%5C%5C%5C%5C%3D%200.6554%20-0.3446%3D%200.3108)
0.3108 is the probability that the sample mean is between 7.8 and 8.2 minutes.
Answer:
![x^2-x-3+\frac{5}{x+6}](https://tex.z-dn.net/?f=x%5E2-x-3%2B%5Cfrac%7B5%7D%7Bx%2B6%7D)
Step-by-step explanation:
![\frac{x^3+5x^2-9x-13}{x+6} \\ \\ =\frac{x^2(x+6)-x^2-9x-13}{x+6} \\ \\ =\frac{x^2(x+6)-x(x+6)-3x-13}{x+6} \\ \\ =\frac{x^2(x+6)-x(x+6)-3(x+6)+5}{x+6} \\ \\ =x^2-x-3+\frac{5}{x+6}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%2B5x%5E2-9x-13%7D%7Bx%2B6%7D%20%5C%5C%20%5C%5C%20%3D%5Cfrac%7Bx%5E2%28x%2B6%29-x%5E2-9x-13%7D%7Bx%2B6%7D%20%5C%5C%20%5C%5C%20%3D%5Cfrac%7Bx%5E2%28x%2B6%29-x%28x%2B6%29-3x-13%7D%7Bx%2B6%7D%20%5C%5C%20%5C%5C%20%3D%5Cfrac%7Bx%5E2%28x%2B6%29-x%28x%2B6%29-3%28x%2B6%29%2B5%7D%7Bx%2B6%7D%20%5C%5C%20%5C%5C%20%3Dx%5E2-x-3%2B%5Cfrac%7B5%7D%7Bx%2B6%7D)